2013
DOI: 10.1017/s0268416013000106
|View full text |Cite
|
Sign up to set email alerts
|

Secularisation and the religious components of marriage seasonality in the Don Army Territory (Southern Russia), 1867–1916

Abstract: The quality of the statistical archives of the Don Army Territory for the period 1867–1916 offers a unique opportunity to compare the denominations present (Orthodox, Old Believers and Coreligionists, Catholics, Lutherans, Jews, Armenian-Gregorians, Lamaist Buddhists and Muslims) in a context of urbanisation, secularisation and industrialisation. The observance of religious interdicts varied between and within denominations depending on levels of urbanisation and the district considered. These contrasts reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Monger (1994) has observed that the superstition about May was also common in England: his analysis is focused on Essex. Bonneuil and Fursa (2013) report the widely held belief among Russian Orthodox populations that May marriages mark couples down for indigence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monger (1994) has observed that the superstition about May was also common in England: his analysis is focused on Essex. Bonneuil and Fursa (2013) report the widely held belief among Russian Orthodox populations that May marriages mark couples down for indigence.…”
Section: Introductionmentioning
confidence: 99%
“…They found that religious norms regarding Lent were respected in all nine communities, but that May credence was found only in the French communities and in one out of three Italian communities. Bonneuil and Fursa (2013) analysed a very interesting area, in terms of religious diversity, "The Don region" in Southern Russia from 1867 to the eve of the Russian Revolution. The analysis of this region allowed them to evaluate how the different religious calendars and popular beliefs associated with the different faiths of the area affected marriage seasonality.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal components st,m(M) for marriages on Figure b appear of similar shape and hierarchy as seasonal components st,falsem+9˜(B) for births on Figure d. For example, no marriages were recorded during March and April in Figure (a) and (b), because of the Lent interdict . Correspondingly, the registration of births takes its lowest value about 9 months later, in December (Figure (d)).…”
Section: Applicationmentioning
confidence: 80%
“…Total numbers of marriages and births, and associated seasonality components, Armenian‐Gregorians, rural district of Rostovskii, 1889–1912. In (a) and (b), no marriages were recorded during March and April, because of the Lent interdict .…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation